The influence of spiritual leadership and its impacts on the reduction of workplace deviant behavior. Issue 3 (12th August 2019) - , Mahyarni
Abstract : Purpose: The purpose of this paper is to examine the influence of spiritual leadership toward spirituality, job satisfaction and reduction of deviant behavior. Design/methodology/approach: A structural model based on WarpPLS (Solimun et al., 2017) is used for data analysis, with the first-order factor analysis based on variables with reflective indicators. Findings: The research findings show that the sustainability of workplace spirituality can stimulate employees' job satisfaction. Accordingly, the direct influence of workplace spirituality on workplace deviant behavior (WDB) is quite major (0.296); this indicates the importance of workplace spirituality for employees in working so it can reduce the WDB. An interesting part about this study is the indirect influence of workplace spirituality on workplace deviant behavior through job satisfaction, which also has a major value (0.208), almost equal to direct influence. This circumstance depicts how workplace spirituality influences workplace deviant behavior, as well as the importance of the improvement of employees' job satisfaction. Originality/value: The originality of this study is primarily placed on the causal relationship between the variables of spiritual leadership and WDB, other than the direct influence; there is also an indirect influence that has a big value, which is the path of spiritual leadership toward workplace deviant behavior through workplace spirituality (−0.248). In other words, workplace deviant behavior is not only influenced directly by spiritual leadership but also by workplace spirituality.